Artificial intelligence image generator assisted descriptive writing - Hamizah, Zahari; Siti Ainun Jariyah, Hassan; Umi Kalsom, Masrom (UPM, 2024)
The use of Artificial Intelligence (AI) is rapidly growing around the world, especially in the education field. In perspective, they were individuals who were concerned with the use of Artificial Intelligence (AI) in education, as they believed that it could potentially cause more harm than good. However, as time passes, we are increasingly exposed to AI’s advantages. It shall not be avoided; instead, we should embrace AI and explore in what way it could be utilised effectively in education. In March 2023, former Higher Education Minister, Datuk Seri Mohamed Khaled Nordin stated that Malaysia would not restrict the use of AI tools such as ChatGPT. However, he emphasized that the implementation must adhere to the guidelines to ensure responsible use of it. This has shown how valuable AI can be and instead of seeing it as a threat, we could explore how AI can assist in teaching and learning.